Effects of pioglitazone versus glimepiride exposure on hepatocellular fat content in type 2 diabetes. Issue 10 (1st May 2013) - Phielix, E.; Brehm, A.; Bernroider, E.; Krssak, M.; Anderwald, C.‐H.; Krebs, M.; Schmid, A. I.; Nowotny, P.; Roden, M.
Abstract : Aims: Thiazoledinediones decrease blood glucose by their insulin‐sensitizing properties. Here, we examined whether pioglitazone plus nateglinide (PIO) interferes with hepatocellular lipid (HCL) content and/or improves insulin sensitivity in well‐controlled non‐obese patients with type 2 diabetes mellitus (T2DM). Methods: Sixteen patients [body mass index (BMI): 28 ± 1 kg/m 2 ; HbA1c: 7.1 ± 0.6%] were studied in a randomized, double‐blind, 12‐week parallel group trial, whereas matched healthy humans [non‐diabetic control subjects (CON), BMI: 26 ± 1 kg/m 2 ] were studied once. Treatment with pioglitazone (30 mg/day) plus nateglinide (PIO arm) to control for glimepiride‐induced insulin secretion was compared to treatment with glimepiride (2 mg/day) plus placebo (GLI arm). Multinuclei magnetic resonance spectroscopy (MRS) was combined with pancreatic normoglycaemic‐two‐step‐insulin clamps and stable isotopes to assess glucose turnover, glucose transport/phosphorylation, HCL and intramyocellular lipid (IMCL) contents, non‐esterified fatty acids (NEFA) and adipokines. Results: At baseline, HCL was approximately 5.6‐fold higher in T2DM (p < 0.05 vs. CON). This was paralleled by approximately doubled leptin : adiponectin ratios (p < 0.05). HCL decreased by approximately 39% (p < 0.05) after PIO and only tended to decrease after GLI (p = 0.12). Treatment with PIO did not affect leptin : adiponectin ratios, but slightly improved (p < 0.05) insulin‐mediated NEFA suppression, which related to lower HCL. PIO further prevented the insulin‐induced increase in IMCL content of soleus and tibialis anterior muscles. Peripheral and hepatic insulin sensitivity, glucose transport and glycaemic control did not change in both groups. Conclusion: Short‐term, low‐dose thiazolidendione treatment improves insulin sensitivity of lipolysis and HCL, without affecting muscle and liver insulin sensitivity. It appears that metabolic PIO action in T2DM is primarily mediated via a decline in HCL associated with greater sensitivity of lipolysis to insulin.